Can climate-smart agriculture help to assure food security through short supply chains? A systematic bibliometric and bibliographic literature review - Morkūnas, Mangirdas; Rudienė, Elzė; Ostenda, Aleksander (Business, Management and Economics Engineering, 2022)
Purpose – This paper aims to reveal potential research possibilities for enhancing climate-smart agriculture through short supply chains.Research question – How can short supply chains assure food security and the promotion of climate-smart agriculture?Research methodology – Bibliographic and bibliometric coupling techniques were employed using data from 1990–2022. The raw data was processed using the VOSviewer 1.6.18 software version.Findings – The results confirm the positive effect of the systemically important relationship between the short supply chain and food security.Research limitations – Climate-smart agriculture is a complex and multifaceted phenomenon. Additional variables may have moderating and mediating effects on the impact of short supply chains on food security.Practical implications – The results establish the importance of having a short supply chain for food security in different aspects of the process from the harvest to the table.Originality and value – This study confirms the rationale for developing shorter food supply chains to assure food security and climate-smart agriculture when possible.